Unterscheiden und herrschen: Ein Essay zu den ambivalenten Verflechtungen von Rassismus, Sexismus und Feminismus in der Gegenwart - Villa, Paula-Irene; Hark, Sabine (transcript, 2017)
The »night in Cologne that changed everything« has changed a lot. However, these changes may have just become more visible. Even though more attention is paid to the concerns of feminists, this is closely interwoven with new kinds of racism and the culturalization of social inequality. One of the most striking paradoxes is the mobilization of gender, sexuality and the concept of women's lib presented by nationalist and xenophobic political parties as well as by conservative governments for the justification of racist, respectively Islamophobic politics of marginalization. If we want to understand how our whole way of living has been put into categories of superiority and subordination and how these subtle differences determine everyone's actions, attitudes and emotions, it is necessary to stop examining sexism, racism and heteronormativity as social ratios independent from each other. The analysis of complex realities requires a way of thinking that focuses on the mutual conditionality of various differences.